1990
DOI: 10.1143/jjap.29.1499
|View full text |Cite
|
Sign up to set email alerts
|

All Screen-Printed CdS/CuInSe2 Solar Cells

Abstract: Thick film technology offers advantages of low cost, product amenability and automation. This technology has been successful in the manufacture of solar cells using CdS/CdTe heterojunctions. It enables the use of the same equipment in various processes involved in manufacturing solar cells. In the present work, n-CdS/p-CuInSe2 solar cells are prepared by screen printing and sintering pastes which contain the semiconductors. An efficiency of 8.75% is achieved. Electron affinity difference, saturation current an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The bandgap was found to vary continuously with molar fraction x, indicating that Zn x Cd 1Ϫx S thin films belong to the amalgamation type. Such variations follow the quadratic equations of the form E g (x) ϭ 2.2 ϩ 0.9x ϩ 0.3x 2 E g (x) ϩ ⌬S 0 ϭ 2.47 ϩ 0.7x ϩ 0.5x 2 The bowing parameters given by the coefficient of the quadratic term in these equations are found to be 0.3 and 0.5 for E g and E g ϩ ⌬S 0 gaps, respectively.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The bandgap was found to vary continuously with molar fraction x, indicating that Zn x Cd 1Ϫx S thin films belong to the amalgamation type. Such variations follow the quadratic equations of the form E g (x) ϭ 2.2 ϩ 0.9x ϩ 0.3x 2 E g (x) ϩ ⌬S 0 ϭ 2.47 ϩ 0.7x ϩ 0.5x 2 The bowing parameters given by the coefficient of the quadratic term in these equations are found to be 0.3 and 0.5 for E g and E g ϩ ⌬S 0 gaps, respectively.…”
Section: Resultsmentioning
confidence: 86%
“…In recent years there has been considerable interest in thin-film semiconductors for use in solar cell devices and thin-film transistors for flat panel displays [1][2][3] Cadmium zinc sulfide is one of the promising materials. The deposition of Zn x Cd 1Ϫx S films has become increasingly important due to the widened industrial applications with a larger number of uses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For further increase in doping concentration, there is again a shift of absorption edge towards the higher wavelengths which indicated the decreasing trend in the optical band gap. Figure [6] indicates that reflectance of the CdS films increased with lower CuCl 2 concentration which indicated that doping promotes the scattering of light waves especially the longer wavelength of the visible region.…”
Section: Resultsmentioning
confidence: 96%
“…Screen printing and sintering is more widely used, non vacuum deposition technique [ 1 ]. Besides of its lower cost equipment and cheapest techniques and lower cost productions, [ 1,2,3,6,7,12 ]. Sharma et al(2004), [ 12] prepared 15  m screen printed CdS films having high absorption coefficient 10 4 cm -1 when sintered at the optimum sintering parameters; which is 500 o C for 10 minutes in air, with the sintering flux; which is CdCl 2 , so it is suitable for window material in heterojunction solar cell.…”
Section: Introductionmentioning
confidence: 99%